THE MODERATING EFFECT OF BOARD INDEPENDENCE ON FIRM ATTRIBUTES OF CORPORATE ENVIRONMENTAL ACCOUNTING DISCLOSURE OF LISTED OIL AND GAS FIRMS IN NIGERIA - Alhaji Zubairu AHMAD; Adamu Adamu Idris; Ismaila Yusuf (Gusau Journal of Accounting and Finance)
This study examines the firm attributes of corporate environmental accounting disclosure (CEAD) of listed oil and gas firms in Nigeria: a moderating effect of board independence. To achieve this, panel data were extracted and used from the annual reports and accounts of twelve (12) sampled listed oil and gas firms in the Nigerian Stock Exchange for a period of ten (10) years (2014-2023). Correlation and ex-post factor design were adopted in collecting data, while ordinary least squares (OLS) multiple regression was employed as technique of data analysis. The study found direct relationship of return on assets, while firm size found no significant impact on the corporate environmental accounting disclosures of listed oil and gas firms in Nigeria. The moderating effect of board independence on the relationship between ROA and CEAD is found to be positively insignificant. Where Firm Size and CEADhave statistical positive significant impact on the corporate environmental accounting disclosure of listed oil and gas firms in Nigeria. It thus, highlighted the need for Securities and Exchange Commission (SEC) to come up with enabling laws towards ensuring that listed oil and gas firms in Nigeria embrace corporate environmental accounting disclosures irrespective of their assets, size and the use of Global Reporting Initiative (GRI) of environmental disclosure index (EDI) to be considered as the most acceptable standard for measuring environmental index by the listed Oil and Gas firms in Nigeria.